Synthesis and reactions of sugar chlorosulphates - Glass, Beverley Dawn (Rhodes University, Faculty of Pharmacy, Pharmacy, 1982)
Summary: Partially chlorosulphated derivatives were synthesised for the purpose of examining the reactions of the chlorosulphonyloxy group in the presence of free hydroxyl groups. The behaviour of the chlorosulphonyloxy group was investigated under acidic conditions. Since sterically favoured chlorosulphonyloxy groups undergo facile replacement by chlorine to form chlorodeoxy sugars, some compounds possessing chlorosulphonyloxy groups which,due to polar and steric effects are not replaced by chloride,were investigated with a view to possible activation of the unfavourable centres towards nucleophilic substitution, thereby making available previously inaccessible chlorodeoxy sugars.
Keywords: Chemical reactions; Sugar -- Synthesis